Evaluasi dan Perencanaan Ulang Kapasitas Saluran Drainase Perumahan Tambak Rejo Indah Waru - Firmansyah, Fero Diky; Saves, Faradlillah; Safitri, Dika Ayu (Jurnal Sains dan Teknologi (JSIT), 2025)
The drainage system in Tambak Rejo Indah Housing, Waru, Sidoarjo, is currently unable to accommodate rainfall runoff effectively, resulting in frequent ponding that disrupts residents’ activities. This study aims to analyze the capacity of the existing tertiary drains across several segments up to the secondary drain and redesign the channel dimensions to meet the required design discharge. Hydrological analysis was carried out using the Log Pearson Type III method to determine the design rainfall, and the Mononobe formula was applied to calculate rainfall intensity. The design discharge was established using a 10-year return period in accordance with the Ministry of Public Works Regulation No. 12/PRT/M/2014. The capacity of the existing drains was compared with the design discharge to identify channels that are insufficient to convey the required flow. New channel dimensions were then determined using a trial-and-error approach until sizes capable of conveying the design discharge were obtained. The analysis shows that several tertiary drains and their respective segments—Tertiary 1 (segments 2–3), Tertiary 2 (segments 4–5), Tertiary 4 (segments 9–10), Tertiary 5 (segments 12–13), Tertiary 6 (segments 16–17 to 26–27), and Tertiary Nilam Barat Main Road (segments 28–31)—are unable to convey the design discharge of 0.80–1.10 m³/s, with existing capacities of only 0.35–0.52 m³/s. Through the trial-and-error process, channel dimensions capable of accommodating the 0.80 × 0.80 m design discharge were obtained, including redesigned dimensions of 0.50 m × 0.50 m for Channel 1 (segment 2–3). This redesign is expected to improve flow efficiency and reduce the potential for ponding within the residential area.